Regeneration and Propagation of Sandalwood - Rangaswami, Rao Sahib S. (Indian Forester, 1937)
Natural reproduction of sandal, general seasons of seeding and the seeding capacity have been discussed. The causes for the absence of seedling growth in certain localities have been traced to seed destruction by various agencies especially rodents. Natural spread of sandal in Salem North Division since 1869 has been worked out. The importance of seed selection by natural agencies such as birds, animals. etc., pointed out. Various artificial methods of sandal propagation have also been described and the merits of artificial regeneration from nursery- grown plants by different methods over direct sewings have been indicated.